Peningkatan Kompetensi Guru PAI dalam Menyusun Proposal Penelitian Tindakan Kelas (PTK) melalui Coaching Terstruktur di Kabupaten Sleman - Heni Wahyu Widayati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This research aims to improve the competency of PAI teachers in the building in drafting the proposal of class action research in Sleman Regency through structured coaching. The subject of research is 9 teachers of junior high School from 3 sub-district, Kalasan Sub-district, Berbah subdistrict and Prambanan subdistrict. The research was conducted for 3 (three) months that may until July 2017, conducted with 2 (two) cycles. The results showed that the understanding of each component of the PTK proposal in cycle I 56.24 on cycle II increased to 83.6. The process assessment score of the 4 stage structured Coaching cycle I amounted to 40.97, on the II cycle increased to 86.8. The result of Cycle I poll is 64.7, in cycle II to 83.6. This demonstrates structured coaching can improve the competency and understanding of teachers in drafting PTK proposals.